2-Phenylethanol and Cyclodextrins: A Review of Properties and Applications - Sidney Goncalo de Lima; Raiane Morais Silva; Andrenilton Ferreira Silva; Allan Kayk Sales Meneses; Charllyton Luis Sena da Costa (2-Phenylethanol and Cyclodextrins: A Review of Properties and Applications, Edition 1, 2025)
Essential oils (EOs), with their distinctive properties, have a wide range of applications in the cosmetic, pharmaceutical, and food industries. Among the various volatile components present in the EOs, 2-phenylethanol (2-PE) stands out, known for its characteristic aroma of rose petals, which has conquered the global market. Despite the challenges associated with the application of EOs in pharmacological studies, such as volatility and low solubility in water, there are effective methodologies that overcome these limitations. In this context, this book presents an innovative approach to the preparation - via spray drying technique, and biotechnological application of 2-PE through the formation of inclusion complexes with cyclodextrins, which have characteristics that help to circumvent the barriers of EOs, in order to evaluate the antinociceptive activity in acute pain models and motor coordination tests. The physicochemical characterization of the inclusion complex was performed using the techniques of Headspace Gas Chromatography coupled to Mass Spectrometry (HS-GC-MS), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and X-ray diffraction (XRD), complemented by computational studies of the complex structures formed. The book is structured in two chapters, addressing in detail the bibliographic study around EOs, 2-PE, cyclodextrins, preparation methods, characterization, and antinociceptive activity. The last chapter is based on an article recently published by our research group, which thoroughly describes the experimental methodology and the results of the characterization and pharmacological tests, which pointed to efficiency in the preparation technique, yield, and significant pain reduction, establishing the 2-phenylethanol inclusion complex as an attractive alternative for commercial production.